Minimal clinically important difference (MCID)-based analysis of single- versus two-level laminectomy for lumbar spinal stenosis: a prospective study - Emir Begagić; Hakija Bečulić; Fahrudin Alić; Anes Mašović; Goran Lakičević; Lemana Buljubašić; Muhamed Haračić (Medicinski glasnik, 2026)
Aim: To compare outcomes and minimal clinically important differences (MCID) between single-level laminectomy (SLL) and two-level laminectomy (TLL) for lumbar spinal stenosis (LSS). Methods: This prospective study included 119 patients with confirmed LSS who underwent SLL or TLL at Cantonal Hospital Zenica from January 2018 to January 2025. Assessments were performed preoperatively and at 1 and 6 months postoperatively using the Oswestry Disability Index (ODI), Swiss Spinal Stenosis Questionnaire (SSSQ), and Visual Analogue Scale (VAS) for back and leg pain, along with evaluation of motor, sensory, and urinary function. MCID values were used to assess meaningful improvement. Results: At six months, SLL patients had lower ODI (15.0 vs. 18.0, p = 0.006), VAS-LB (3.0 vs. 5.0, p < 0.001), and SSSQ scores (17.2 vs. 21.6, p < 0.001) than TLL patients. Motor deficits (14.8% vs. 35.5%, p = 0.019) and urinary dysfunction at 1 month (5.7% vs. 22.6%, p = 0.013) were less frequent in SLL. More SLL patients achieved MCID for ODI (80.7% vs. 58.1%, p = 0.024) and SSSQ (73.9% vs. 48.4%, p = 0.017) at 6 months, with TLL patients 28% and 34% less likely to reach MCID for ODI and SSSQ, respectively. No significant differences were found preoperatively or at 1 month. Conclusion: The study suggests that SLL and TLL have comparable outcomes, with a slight tendency toward better functional improvement and fewer deficits after SLL.
Keywords: degenerative spinal stenosis; disability evaluation; nerve root compression; outcome assessment